2011
DOI: 10.1121/1.3588128
|View full text |Cite
|
Sign up to set email alerts
|

A new connection: Enhanced hearing ability in the New Zealand bigeye, Pempheris adspersa.

Abstract: Recently the bigeye, Pempheris adspersa, has been found to be one of the few sound producing fish found in the temperate marine waters of New Zealand. An initial crude morphological examination of this species found a special connection, analogous to that of the well-defined laterophysic connection, between the otic capsule and the lateral line recess. The aim of the present study was to characterize the hearing ability of the bigeye using auditory evoked potentials, understand the role of this special connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Severing the specialised hearing connection in the bigeye increases their hearing sensitivity by 15-20dB re. 1Pa (Radford et al, 2011). Our current study in conjunction with this previous research provides further evidence that it is the presence and the ability of the ancillary hearing structures to convey pressure sensitivity to the inner ear that differentiates the hearing ability of different species of fish.…”
Section: Mssupporting
confidence: 76%
See 2 more Smart Citations
“…Severing the specialised hearing connection in the bigeye increases their hearing sensitivity by 15-20dB re. 1Pa (Radford et al, 2011). Our current study in conjunction with this previous research provides further evidence that it is the presence and the ability of the ancillary hearing structures to convey pressure sensitivity to the inner ear that differentiates the hearing ability of different species of fish.…”
Section: Mssupporting
confidence: 76%
“…The triplefin has no swim bladder so theoretically has no capability to detect a pressure stimulus, and this was represented in their pressure hearing sensitivity by their being the least sensitive of the three species examined. The two other species tested in the present study have ancillary hearing structures; Weberian ossicles for the goldfish (Von Frisch, 1938;Fay and Popper, 1974) and an otolaterophysic connection for the bigeye (Radford et al, 2011). It has been shown that as the Weberian ossicles develop in the zebrafish (Danio rerio) and connect the inner ear to the swim bladder, the hearing range increases from 1000 to 4000Hz and the fish become more sensitive to sound (Higgs et al, 2002).…”
Section: Msmentioning
confidence: 77%
See 1 more Smart Citation